A regional bolus tracking and real‐time B1 calibration method for hyperpolarized 13C MRI. Issue 2 (18th September 2018) - Tang, Shuyu; Milshteyn, Eugene; Reed, Galen; Gordon, Jeremy; Bok, Robert; Zhu, Xucheng; Zhu, Zihan; Vigneron, Daniel B.; Larson, Peder E. Z.
Abstract : Purpose: Acquisition timing and B1 calibration are two key factors that affect the quality and accuracy of hyperpolarized 13 C MRI. The goal of this project was to develop a new approach using regional bolus tracking to trigger Bloch‐Siegert B1 mapping and real‐time B1 calibration based on regional B1 measurements, followed by dynamic imaging of hyperpolarized 13 C metabolites in vivo. Methods: The proposed approach was implemented on a system which allows real‐time data processing and real‐time control on the sequence. Real‐time center frequency calibration upon the bolus arrival was also added. The feasibility of applying the proposed framework for in vivo hyperpolarized 13 C imaging was tested on healthy rats, tumor‐bearing mice and a healthy volunteer on a clinical 3T scanner following hyperpolarized [1‐ 13 C]pyruvate injection. Multichannel receive coils were used in the human study. Results: Automatic acquisition timing based on either regional bolus peak or bolus arrival was achieved with the proposed framework. Reduced blurring artifacts in real‐time reconstructed images were observed with real‐time center frequency calibration. Real‐time computed B1 scaling factors agreed with real‐time acquired B1 maps. Flip angle correction using B1 maps results in a more consistent quantification of metabolic activity (i.e, pyruvate‐to‐lactate conversion, k PL ). Experiment recordings are provided to demonstrate the real‐time actions during the experiment. Conclusions: The proposed method was successfully demonstrated on animals and a human volunteer, and is anticipated to improve the efficient use of the hyperpolarized signal as well as the accuracy and robustness of hyperpolarized 13 C imaging.